4CPS-156 A rare case and an effective drug therapy: off-label use of tacrolimus in a paediatric dysimmune disease. (2nd March 2018) - Cingolani, L; Gatti, S; Berardi, MA; Ortenzi, G; Vallorani, M; Pompilio, A; Garzone, AMF; Andresciani, E; Leoni, S; Catassi, C; Moretti, V
Abstract : Background: A 7 month child with an unremarkable previous medical history presented with a history of 18 days of severe secretory diarrhoea. Clinical and histological features were consistent with autoimmune enteropathy. The patient could not tolerate foods, and was started on total parental nutrition (TPN) and i.v. Methylprednisolone, without substantial clinical improvement. Confirmed resistance to traditional therapy and consulted hospital pharmacists. The use of tacrolimus was identified as the best option. Purpose: The aim of this work is to report several aspects of the hospital pharmacy's involvement in the management of a difficult case, including off-label approval, compounding, alternative therapies, nutritional support and costs. Material and methods: Being not registered for use, the corporate formal procedure for off-label drugs was submitted to 'Corporate Commission off-label' involving a designated pharmacist, pharmacologist and clinic. Parents signed formal 'informed consent' and medical records were verified. Tacrolimus suspension 0.5 mg/ml to 40 ml was prepared according to the scientific literature and compounding formulas, using a basic vehicle for the compounding of oral liquid dosage forms (stability 56 days, storage at 24°C–26°C). An appropriate personalised TPN was formulated. Results: Drugs: i.v. methylprednisolone was used at 1.5 mg/kg/day for 1 month, with dose tapering in 3 months. Tacrolimus was used as a unique therapy for 5 months (mean dose: 0.15 mg/kg/day), and associated with azathioprine at 2.5 mg/kg/day for 2 months. Twenty-two bottles of tacrolimus were prepared for €730 overall. Tacrolimus and azathioprine were stopped during a fungal infection, after which only azathioprine was restarted. No adverse reactions were reported. Nutrition: TPN for 3 months with soy-based lipid mixture (50% soybean oil:50% MCT 3 g/kg/day) and for 11 months with fish-oil lipid mixture (30% soybean oil:30% MCT:25% olive oil:15% fish oil 2.5 g/kg/day). Optimal tolerance to PN and appropriate weight gain. PN was progressively reduced and an elemental liquid oral formula introduced. Overall, after 16 months, clinical and histological condition substantially improved and the patient currently tolerates enteral nutrition with elemental formula plus azathioprine. Conclusion: Rare paediatric diseases are always a challenge for the hospital medical staff. In this case the medical plan is to slowly reintroduce hypoantigenic foods and stop azathioprine. Given the disease rarity, we hope to increase available data and help the management of similar cases. References and/or Acknowledgements: Thanks to Corporate Commission off-label No conflict of interest